Effects of maturity of citrus fruits on their stalks cutting force - Wang, Yi; Liu, Dun; Li, Yali; Zhao, Hongmei; Yang, Changhui; Zhang, Yitan (International Journal of Agricultural and Biological Engineering, 2022)
When the citrus harvesting robot harvests citruses, the mechanical properties of citrus stalks have an important influence on the success rate of the citrus harvesting robot. During the harvesting, the maturity of citrus fruits not only determined the harvesting time of citrus fruits but also affected the mechanical properties of citrus fruit stalks. In this study, the changes in the cutting force of citrus fruit stalks were described during the maturity of citrus fruits, and the effect of the maturity on the cutting force of stalks was clarified, so as to determine the harvesting time with the minimum cutting force required for harvesting citrus fruits by the harvesting robot. During the maturity, the relevant parameters of fruit maturity, such as the hardness, pH, and solid solution content of citrus fruits, were monitored. The results showed that there is a significant correlation between the hardness, pH, the solid solution content of citrus fruits, and the cutting force of citrus fruit stalks during maturity. The single-factor mechanical model of hardness, pH, solid solution content of citrus fruits, and the cutting force of citrus fruit stalks were established based on the data of 2019, which were verified through tests in 2020. The test results are as follows: during the ripening period of citrus fruits, the fruit hardness varies in the range of 0.13-0.31 MPa, the hardness changes by 0.02 MPa, and the cutting force changes by about 2.0-6.0 N; the pH of the citrus fruits changes in the range of 2.8-4.0, and the cutting force changes by about 1.5-2.2 N for every 0.1 change in the pH; the variation range of fruit solid solution content is 6.5%-9.0%, and for every 0.2% change in solid solution, the cutting force of citrus fruit stalks changes by about 1.25-2.0 N. The mechanical models can predict the cutting force required to cut off citrus fruit stalks according to the relevant parameters of citrus fruit maturity and can provide a reference for effectively evaluating the required cutting force.Keywords: citrus fruit harvesting, cutting force of citrus fruit stalks, citrus fruit maturity, mechanical regression modelDOI: 10.25165/j.ijabe.20221505.7063Citation: Wang Y, Liu D, Li Y L, Zhao H M, Yang C H, Zhang Y T. Effects of maturity of citrus fruits on their stalks cutting force. Int J Agric & Biol Eng, 2022; 15(5): 23–30.